Tribological Effects of Additive Hybrid ZrO2/Al2O3 in Bio-Lubrication / Mimi Azlina Abu Bakar ... [et al.] - Abu Bakar, Mimi Azlina; Kasolang, Salmiah; Ahmad, Mohamad Ali; Herman, Dedisaputra (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Bio-based oil application has increased dramatically in the lubrication industry as an alternative to conventional petroleum-based oil. Due to a huge demand towards sustainability, it is extremely important to make an effort in promoting alternative for synthetic bio-lubricant as an alternative to synthetic oil. In this study of, tribological properties the palm oil, bio-lubricant modified with hybrid of ZrO2/Al2O3 micro-particles as an additive was investigated. The additives was mixed using ultrasonic vibrator to ensure homogenous mixing and consistent characteristic. The tribological performance was investigated using a pin on disk at different loads of 5 kg, 10 kg, 15 kg and 20 kg. It was tested at different weightage percentages of micro-additive varied between 0.1 to 1 wt%. Tribological testing was conducted to obtain the performance of ZrO2 micro-particle, Al2O3 micro-particle and hybrid of ZrO2/Al2O3 micro-particle. It was observed that the coefficient of friction (COF) for zirconia (ZrO2) and alumina oxide (Al2O3) was found to be the lowest at 0.1 wt%.